(untitled) - Bear, Jacob (Mineola, N.Y., 2007)
This text explores the laws and equations governing the flow and storage of groundwater in aquifers. It provides groundwater hydrologists — as well as engineers and planners dealing with the development and management of groundwater resources — with all the necessary tools to forecast the behavior of a regional aquifer system. 1979 edition.
Thủy lực nước ngầm
Keywords: Groundwater flow,Groundwater,Hydrodynamics; Dòng chảy nước ngầm,Thuỷ động lực học,Nước ngầm